2005
DOI: 10.1002/poc.892
|View full text |Cite
|
Sign up to set email alerts
|

High chemoselectivity of CS dipolarophile in 1,3‐dipolar cycloaddition of nitrilimines and 1,2,4‐triazepin‐5‐one derivatives: experimental, theoretical and X‐ray study

Abstract: Substituted 2,7‐dimethyl‐3‐thioxo‐3,4,5,6‐tetrahydro‐2H‐[1,2,4]triazepin‐5‐one reacts as a dipolarophile with several N‐aryl‐C‐ethoxycarbonylnitrilimines, in equimolar quantities, to give, in all cases, two types of products: diethyl 3‐(p‐aryl)‐2‐[N′‐(p‐aryl)‐N′‐(2′,7′‐dimethyl‐5′‐oxo‐5′,6′‐dihydro‐2H‐[1,2,4]triazepin‐3′‐yl)‐hydrazino]‐2,3‐dihydro[1,3,4]thiadiazole‐2,5‐dicarboxylate (3a–3c in 20–25% yield) and ethyl 4‐(p‐aryl)‐5‐imino‐1,4‐dihydro[1,3,4]thiadiazole carboxylate (4a–4c in 45–50% yield). When 1:2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…An important contribution of these descriptors is analyzing the cycloaddition reactions 159,160,270–290 . Through various studies, it is noticed that a Diels‐Alder reaction (DAR) proceeds via a nonpolar pericyclic mechanism when there exists a small difference in electrophilicity values of the diene and the dienophile, whereas for a significant difference, it follows a polar mechanism.…”
Section: Applicationsmentioning
confidence: 99%
“…An important contribution of these descriptors is analyzing the cycloaddition reactions 159,160,270–290 . Through various studies, it is noticed that a Diels‐Alder reaction (DAR) proceeds via a nonpolar pericyclic mechanism when there exists a small difference in electrophilicity values of the diene and the dienophile, whereas for a significant difference, it follows a polar mechanism.…”
Section: Applicationsmentioning
confidence: 99%
“…The main classes of reactions for which the mechanisms have been analyzed in terms of global and local electrophilicities comprise 1,3-dipolar cycloaddition reactions, specific cycloaddition reactions such as Diels−Alder reactions , with varied diene−dienophile pairs, and other cycloaddition reactions. A typical Diels−Alder reaction will follow a nonpolar pericyclic mechanism if the electrophilicity difference between the diene and the dienophile is small whereas a polar mechanism will be followed for a large value of this difference.…”
Section: 4 Chemical Processesmentioning
confidence: 99%
“…As it has been indicated in the experimental part, in spite of the presence of four dipolarophile sites in 1, these reactions take place with a total chemoselectivity; only the C=S double bond participates as dipolarophile in these 13DC reactions. 22 According to the experimental result, we decided to perform the computational study of the addition of the nitrilimine 2g to the C=S double bond of 1. For this 13DC reaction, the two regioisomeric channels associated to the addition of 2g to the unsymmetric C=S double bond of 1 were studied.…”
Section: Study Of the 13-dipolar Cycloaddition Reaction Between 3-thmentioning
confidence: 99%
“…14,15 They are reported as excellent ligands with transition metals inducing a large application in organometallic chemistry. 16,17 In the context of our current interest in the synthesis of novel heterocyclic compounds, [18][19][20][21][22] susceptible to have biological activity, we have now studied the 1,3-dipolar cycloaddition (13DC) reaction between 6-dimethylaminomethylene-3-thioxo-[1,2,4]-triazepin-5-one 1 and C,N-disubstituted nitrilimines 2a-f (Scheme 1), which were generated in situ from the appropriate precursors and triethylamine. However, we have found that along the purification of reaction mixture by column chromatography, the corresponding spirocycloadducts 3a-f were transformed into the bicyclic compounds 4a-f and 5a-f. Herein, we present the experimental results of the title reaction together with a theoretical study providing an explanation for the formation of the two new bicyclic compounds.…”
Section: Introductionmentioning
confidence: 99%